2021
DOI: 10.1513/annalsats.202009-1131oc
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Iron in Pulmonary Arterial Hypertension. Two Randomized Crossover Trials

Abstract: Switzerland, who remained independent of the study design and had no role in data collection or analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 23 publications
0
20
0
2
Order By: Relevance
“…The definition of iron deficiency varies among clinical trials, involving biomarkers such as ferritin, transferrin saturation (TSAT), soluble transferrin receptor (sTfR), and sTFRF index (sTfR/log ferritin) (Table 5). 13 Chronic disease with prominent inflammation can raise ferritin and lower serum iron levels and TSAT, but it does not influence sTfR 23 . The sTfR index and C‐reactive protein level may be the best prognostic biomarker for clinical impairment associated with iron deficiency.…”
Section: Iron Deficiency In Pahmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of iron deficiency varies among clinical trials, involving biomarkers such as ferritin, transferrin saturation (TSAT), soluble transferrin receptor (sTfR), and sTFRF index (sTfR/log ferritin) (Table 5). 13 Chronic disease with prominent inflammation can raise ferritin and lower serum iron levels and TSAT, but it does not influence sTfR 23 . The sTfR index and C‐reactive protein level may be the best prognostic biomarker for clinical impairment associated with iron deficiency.…”
Section: Iron Deficiency In Pahmentioning
confidence: 99%
“…The only randomized, double‐anonymized, placebo‐controlled studies conducted on IV FCM was conducted by Howard and colleagues 23 . They conducted two 12‐week crossover studies, in which 39 patients in Europe received FCM 1000 mg (or 15 mg/kg if body weight was <67 kg) or saline, and 17 patients in China received iron dextran (20 mg of iron per kilogram of body weight) or saline.…”
Section: Iron For Iron Deficiency In Pahmentioning
confidence: 99%
“…As iron deficiency is associated with a poor prognosis in patients with idiopathic pulmonary arterial hypertension 20) , iron deficiency is expected as a therapeutic target for pulmonary hypertension. As regards iron repletion for patients with pulmonary hypertension, recent two randomized, double-blind studies of intravenous iron versus placebo showed that iron repletion to pulmonary hypertension patients with iron deficiency without overt anemia provided no significant clinical benefit at 12 weeks after intravenous iron administration 28) . Besides systemic deficiency without overt anemia, as defined by raised levels of soluble transferrin receptor, is common in patients with idiopathic pulmonary arterial hypertension; further, it is associated with disease severity and poor clinical outcome 20) .…”
Section: Cellular Iron Transport In Pulmonary Arteriosclerosismentioning
confidence: 99%
“…In this issue of AnnalsATS , Howard and colleagues (pp. 981–988 ) report the results from these investigations ( 13 ). In a study performed in Europe, ferric carboxymaltose or placebo was given as a single infusion at a dose of 1,000 mg (or 15 mg/kg if body weight was <67 kg) to 39 patients, and in a study conducted in China, iron dextran (20 mg iron/kg) body or placebo was given as a single infusion to 17 patients.…”
mentioning
confidence: 99%